A patient with acute hepatitis E and intractable vomiting: a case report - Deng, Kui; Dong, Xiao-Qin; Xu, Dong (Frontiers in Medicine, 2025)
We reported a patient with acute hepatitis E who had recurrent vomiting and dizziness that are uncommon in other patients with hepatitis E. The patient developed dizziness 1 month ago prior, accompanied by yellow urine, sclera, and staining of the skin. Half a month prior, the patient gradually developed fatigue and a poor appetite, accompanied by nausea, aversion to oil, loss of appetite, and itching of the skin. The patient turned out to have an acute hepatitis E infection and was hospitalized for more than a month with repeated vomiting and dizziness. He was treated conservatively with drugs for various reasons. After more than 1 month of medication and rest, the patient's vomiting and dizziness symptoms improved significantly, and follow-up found that the recovery was good.